Analisis Kinerja Anggaran Belanja pada Badan Pusat Statistik Kabupaten Aceh Barat - Urrahmah, Reza; Darmayanti, Cici (Regress: Journal of Economics & Management, 2022)
The government in regulating and controlling budget funds must of course look at budget performance which aims to assess and measure the amount of budget realization contained in the financial statements. The Central Statistics Agency of West Aceh is an analysis unit in this study and the 2018-2021 budget realization report is the observation unit. This study uses quantitative descriptive methods that are processed using shopping performance analysis tools including shopping variance analysis, growth analysis, shopping harmony analysis, and shopping efficiency ratio. The results of his research are (1) When viewed from the Variance of Spending from 2018 to 2021, the Central Statistics Agency of West Aceh Regency has made good budget savings and the realization of its budget has never exceeded the budget given; (2) Budget performance in terms of the results of the expenditure growth ratio at bps in West Aceh is not good because the results of the analysis from 2018-2021 showed negative results; (3) In view of the analysis of spending harmony at the Central Statistics Agency of West Aceh Regency during the 2018-2021 fiscal year, the largest use of the expenditure budget is allocated to operating expenditures; (4) Judging from the expenditure efficiency ratio at the Central Statistics Agency of West Aceh Regency during the 2018-2021 fiscal year, it is included in the efficient criteria.